Woodpaths : Chemins qui mènent nulle part. - Finlay, Ian Hamilton; Heidegger, Martin (Surrey : Wild Hawthorn Press.)
Note in book: The first two sentences are by Martin Heidegger, the third has been added by Ian Hamilton Finlay. The decorations are by Solveig Hill. Printed by Peter Knee, Surrey, England for the Wild Hawthorn Press, Little Sparta.
Engels
boek
Keywords: Finlay, Ian Hamilton; Heidegger, Martin; Hill, Solveig